Narratives of displacement and poverty: the intersections of policy and the shared experience of the everyday - Williams, Lucy (Frontiers in Human Dynamics, 2023)
An extensive, and growing, global literature on the experience of people subject to migration control shows how state actions to “manage” migration and human mobility results in poverty and destitution. There is also a large body of evidence indicating how neo-liberal policy, alongside deeply embedded structures of privilege and inequality lead to the economic deprivation of fully entitled, “citizen” populations. Despite the commonality of disadvantage between these two groups—migrants and citizens—the parallels in experience of structures that create and maintain their impoverishment have rarely been explored. Close attention to the stories told by people with lived experience of poverty, as citizens or as migrants, challenges the normative assumptions about belonging and entitlement, deservingness and opportunity that underpin policy-making on both migration and social inequality. This essay argues that listening to, and engaging with, the stories of people in poverty is an important corrective to normative ideas about who can benefit from state support. Focusing on the UK, my aim is to explore the position of people subject to migration control alongside others living in poverty—marginalized and made precarious not by displacement but by deprivation, stigma and punitive welfare systems. Paying close attention to the stories people tell cuts through the official, normative positioning of people as outsiders whether as foreigners or as marginalized citizens. Stories thus reveal the technologies of power and oppression at work in everyday settings. Drawing on concepts including Butler's ideas of grievability and Mbembe's necropolitics I reflect on how welfare management systems and the “so-called” hostile environment, reduce the capacity of migrants and others to act as purposeful human beings. I hope to reveal the technologies of power and oppression at work in everyday settings and will argue that careful, attentive listening to human stories can challenge the imposition of normative discourses on the voiceless and encourage narratives that embrace complexity.